Assistance in Planning the Construction of Closed House Chicken Coops in Kedungrejo Village, Rembang Regency - Masvika, Hendra; Kusrin, Kusrin; Pudjihardjo, Hari Setijo; Purnijanto, Bambang (LP2M of Institute for Research and Community Services - UIN Walisongo, 2023)
The high demand for poultry production has recently prompted members of the Mbesi Chicken Farmers Group in Kedungrejo Village, Rembang Regency, to focus on increasing productivity by optimizing the construction of their chicken coops. The closed-house system, suitable for the local environment and weather conditions, has been identified as the most appropriate type of poultry coop. However, the construction process is often outsourced, resulting in frequent design changes and price increases passed on to the breeders. To address this issue, the present Community Service (PkM) activity was carried out to assist farmers in creating design drawings for closed-house poultry coop buildings. The Participatory Action Research (PAR) method, involving direct mentoring, was employed to facilitate farmers in the process. The outcome of this community service was the submission of detailed design drawings for closed-house poultry coop buildings. An evaluation was conducted using pre-test and post-testassessments, revealing that 80% of participants could read and comprehend the design drawings for planning a closed-house chicken coop system. Accordingly, the findings indicated an improvement in the partner's competence in interpreting design drawings.